2021
DOI: 10.1111/jog.14872
|View full text |Cite
|
Sign up to set email alerts
|

The level of depression, anxiety, and sleep quality in pregnancy during coronavirus disease 2019 pandemic

Abstract: Aim: We aimed to evaluate the mental health and sleep quality of pregnant women in different trimesters during coronavirus disease 2019 (COVID-19) pandemic and investigate the effect of quarantine and new lifestyle changes that come into our lives with pandemic with on this subject. Methods: It was conducted on pregnant women (n = 149) who attended routine pregnancy prenatal visit during their pregnancy weeks. The data were collected using sociodemographic and clinical data form, Pittsburgh Sleep Quality Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
17
1
Order By: Relevance
“…However, a study in Zhoushan, China, found that the prevalence of both anxiety and depression was highest in the first trimester and lowest in the second trimester, according to the Self-Rating Anxiety Scale and Self-Rating Depression Scale [ 25 ]. Another Turkish study found that a larger number of women had depressive symptoms in their third trimester [ 8 ]. These disparities may be attributable to the assessment tools used and differences in study settings and populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study in Zhoushan, China, found that the prevalence of both anxiety and depression was highest in the first trimester and lowest in the second trimester, according to the Self-Rating Anxiety Scale and Self-Rating Depression Scale [ 25 ]. Another Turkish study found that a larger number of women had depressive symptoms in their third trimester [ 8 ]. These disparities may be attributable to the assessment tools used and differences in study settings and populations.…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish population-wide study reported that the percentage of expectant mothers who suffer from at least one psychiatric illness is approximately 14% [ 7 ]. A Turkish study that evaluated the state of pregnant women during different trimesters of pregnancy has observed that depression, anxiety, and defective sleep quality were higher in the third trimester compared to the first and second trimesters [ 8 ]. A 2020 Pakistani study that explored antenatal stress and its associations amongst pregnant Punjabi women also reported high-stress levels amongst 42.2% of their respondents and concluded that it was mostly associated with low-income status, non-involvement of the respondent in household decision-making, desire for a son rather than a daughter, and experience of birth complications in past pregnancies [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women in the third trimester report having higher scores of experiencing anxiety (Hamzehgardeshi et al, 2021). This could be because pregnant women in the third trimester feel anxious about various things, such as whether they can give birth normally, preparing for childbirth, worrying about contracting COVID-19 in the hospital environment and infecting their babies (Çolak et al, 2021;. The results of previous studies, gestational age and anxiety levels have no correlation (Effati-Daryani et al, 2020;Kahyaoglu Sut & Kucukkaya, 2021;Skouteris et al, 2009;van de Loo et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…There was a considerable disparity between the change in getting health care and the concern because mobile applications usage by pregnant women during the COVID-19 pandemic (OzkanSat & Sozbir, 2021). During COVID-19, high levels of depression, anxiety & stress experiences of prenatal trauma, antenatal attachment, low family income, lack of physical exercise, health anxiety, sleep disorders, low social support, and having a COVID-19 infected person among relatives (Filippetti, Clarke & Rigato, 2022;Stampini et al, 2021;Khazaeian, Khazaeian & Fathnezhad-kazemi, 2021;Ravaldi et al, 2020;Jelicic, et al,2021;Colak et al, 2021;Kajdy et al, 2021&Yu, et al, 2020. High on psychological stress, who are unable to attend the delivery of critical obstetric visits and receive support from friends, family, and birthing classes (Leiker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%